COMPARING WATER-FALL MODEL AND SPIRAL MODEL ON SYSTEM INFORMATION PATIENT SERVICE DESIGN (Case Study at PUSKESMAS PANCORAN MAS DEPOK) - Widianti, Santi (Universitas Gunadarma, 2009)
In the information era at this time all humankind in each aspect of his life expect a fast and exact service both in the healthy situation and the situation to be sick. Likewise his matter with that is hop for by all the elements of the framer of the system in the Pancoranmas community health centre, the patient 's satisfaction is not enough only well not him the community health centre, professional him the doctor along with medical him, but also depend from fast and to be precise the information service that is need by the patient. By using aids of the system plan, then is develop by an information system so as facilitat in the matter kept, modified, process and access the data in accordance with the requirement, from this system it is hop time that is us to access the data like the patient 's data, medicine, the story of the health of the patient could be more fast, efficient and safe in his storage and accurate, with the availability of quality information and the good communications network interdepartmental will increase the productivity of his officials, this plan of the information system if being us is the opportunity for the community health centre to increase the service and professionalism.Keyword(s) : information system, puskesmas, spiral, water-fallSubject description: K.6.Management of Computing and Information | K.6.3. Software Management | Software Development